The effects of leptin on human cytotrophoblast invasion are gestational age and dose-dependent - Rumer, Kristen K.; Sehgal, Shilpi; Kramer, Anita; Bogart, Kevin P.; Winn, Virginia D. (Frontiers in Endocrinology, 2024)
Introduction Leptin and its receptors are expressed by the human placenta throughout gestation, yet the role of leptin in early human placental development is not well characterized. Leptin is overexpressed in the placentas from preeclamptic (PE) pregnancies. PE can result from the impaired invasion of fetal placental cells, cytotrophoblasts (CTBs), into the maternal decidua. We hypothesized that elevated leptin levels would impair human CTB invasion. Methods The effects of leptin on the invasion of human CTBs were evaluated in three cell models, HTR-8/SVneo cells, primary CTBs, and placental villous explants using invasion assays. Further, leptin receptor expression was characterized in all three cell models using RT-PCR. Further phosphokinase assays were performed in HTR-8/SVneo cells to determine signaling pathways involved in CTB invasion in response to differential leptin doses. Results We found that, prior to 8 weeks gestation, leptin promoted CTB invasion in the explant model. After 11 weeks gestation in explants, primary CTBs and in HTR-8/SVneo cells, leptin promoted invasion at moderate but not at high concentrations. Further, leptin receptor characterization revealed that leptin receptor expression did not vary over gestation, however, STAT, PI3K and MAPK pathways showed different signaling in response to varied leptin doses. Discussion These data suggest that the excess placental leptin observed in PE may cause impaired CTB invasion as a second-trimester defect. Leptin’s differential effect on trophoblast invasion may explain the role of hyperleptinemia in preeclampsia pathogenesis.